2011
DOI: 10.1093/humrep/der182
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Mullerian hormone-tailored stimulation protocols improve outcomes whilst reducing adverse effects and costs of IVF

Abstract: Although large, prospective, multicentre studies are indicated, we have clearly demonstrated that individualized, AMH-guided, controlled ovarian hyperstimulation protocols significantly improved positive clinical outcomes, reduced the incidence of complications and reduced the financial burden associated with assisted reproduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
58
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(61 citation statements)
references
References 57 publications
2
58
1
Order By: Relevance
“…purified menotropins (human menopausal gonadotropins compared with recombinant FSH) may also help to reduce the risk of high response and also improve outcomes among women with high AMH levels, regardless of agonist or antagonist protocol (Arce et al, 2014). These findings are supported by a retrospective study that evaluated outcomes for women assigned to a stimulation protocol based on basal FSH and age (conventional determination) compared with AMH levels (Yates et al, 2011). Patients in the conventional group received either a long GnRH agonist downregulation protocol (low FSH) or a co-flare GnRH agonist protocol (high FSH) with human menotropins of 150 or 300 IU depending on patient age; those in the AMH-tailored group received a GnRH antagonist protocol with 300 IU of menotropins (low AMH), a long GnRH agonist downregulation protocol with 200 IU of recombinant FSH or 225 IU of menotropins (moderate AMH), or a GnRH antagonist protocol with 150 IU of menotropins.…”
Section: Amh: the Evidence As A Predictive Methodsmentioning
confidence: 96%
“…purified menotropins (human menopausal gonadotropins compared with recombinant FSH) may also help to reduce the risk of high response and also improve outcomes among women with high AMH levels, regardless of agonist or antagonist protocol (Arce et al, 2014). These findings are supported by a retrospective study that evaluated outcomes for women assigned to a stimulation protocol based on basal FSH and age (conventional determination) compared with AMH levels (Yates et al, 2011). Patients in the conventional group received either a long GnRH agonist downregulation protocol (low FSH) or a co-flare GnRH agonist protocol (high FSH) with human menotropins of 150 or 300 IU depending on patient age; those in the AMH-tailored group received a GnRH antagonist protocol with 300 IU of menotropins (low AMH), a long GnRH agonist downregulation protocol with 200 IU of recombinant FSH or 225 IU of menotropins (moderate AMH), or a GnRH antagonist protocol with 150 IU of menotropins.…”
Section: Amh: the Evidence As A Predictive Methodsmentioning
confidence: 96%
“…AMHderived assessment of ovarian reserve has been used to optimize individual treatment strategies and to predict poor or excessive ovarian response (1,2) and live birth rate (3,4). Firstgeneration commercial AMH ELISAs were developed independently by Diagnostic Systems Laboratories (DSL) and Immunotech (IOT).…”
mentioning
confidence: 99%
“…Given the ability of AMH to predict both a poor and excessive ovarian response, using AMH to tailor ovarian stimulation has been proposed by several investigators (5)(6)(7). The ability of AMH to accurately identify women at risk of ovarian hyperstimulation syndrome (OHSS) is potentially its greatest utility, as we now have a variety of techniques available to us to reduce or completely eliminate the risk of this potentially fatal complication (8)(9)(10).…”
mentioning
confidence: 99%
“…The ability of AMH to accurately identify women at risk of ovarian hyperstimulation syndrome (OHSS) is potentially its greatest utility, as we now have a variety of techniques available to us to reduce or completely eliminate the risk of this potentially fatal complication (8)(9)(10). Initial studies using an AMH stratified approach to individualize treatment have demonstrated a significant reduction in OHSS (6) while not compromising live-birth rates (11).…”
mentioning
confidence: 99%